Pressure Inactivation of Bacillus Endospores - Margosch, Dirk (American Society for Microbiology, 2004)
The inactivation of bacterial endospores by hydrostatic pressure requires the combined application of heat and pressure. We have determined the resistance of spores of 14 food isolates and 5 laboratory strains of Bacillus subtilis, B. amyloliquefaciens, and B. licheniformis to treatments with pressure and temperature (200 to 800 MPa and 60 to 80°C) in mashed carrots. A large variation in the pressure resistance of spores was observed, and their reduction by treatments with 800 MPa and 70°C for 4 min ranged from more than 6 log units to no reduction. The sporulation conditions further influenced their pressure resistance. The loss of dipicolinic acid (DPA) from spores that varied in their pressure resistance was determined, and spore sublethal injury was assessed by determination of the detection times for individual spores. Treatment of spores with pressure and temperature resulted in DPA-free, phase-bright spores. These spores were sensitive to moderate heat and exhibited strongly increased detection times as judged by the time required for single spores to grow to visible turbidity of the growth medium. The role of DPA in heat and pressure resistance was further substantiated by the use of the DPA-deficient mutant strain B. subtilis CIP 76.26. Taken together, these results indicate that inactivation of spores by combined pressure and temperature processing is achieved by a two-stage mechanism that does not involve germination. At a pressure between 600 and 800 MPa and a temperature greater than 60°C, DPA is released predominantly by a physicochemical rather than a physiological process, and the DPA-free spores are inactivated by moderate heat independent of the pressure level. Relevant target organisms for pressure and temperature treatment of foods are proposed, namely, strains of B. amyloliquefaciens, which form highly pressure-resistant spores.